Increasingly diverse coral reef fishes are threatened by unsustainable fishing in Palau - Christina Muller Karanassos; Alyssa Marshell; Barrett Wolfe; Steve Lindfield; Jeremy Prince; Nils C. Krueck (Reviews in Fish Biology and Fisheries, 2026)
Reef fisheries underpin the economy, culture, and food security of Indo-Pacific island nations, yet many target species are depleted due to inadequate management. Despite its reputation as a regional leader in fisheries management, Palau has experienced declines among key reef fish species, necessitating a comprehensive stock status assessment amid ongoing discussions to lift the national export ban. Conventional stock assessments are not feasible for most species due to limited data. To address this, we compiled life history information and applied data-limited, length-based stock assessment methods across 32 parameter scenarios. Analyses were based on a decade of fishery-dependent landing data (2014–2024) for 45 key species, with comparisons to historical landings (1976–1991) to evaluate changes in catch composition. Using Length-Based Spawning Potential Ratio as the primary assessment method, we found most species are in poor condition: 24.4% classified as “Depleted”, 51.1% “Vulnerable”, and 17.8% “Depleting”. Only 6.7% met criteria for “Sustainable” status (spawning potential ratio > 40% of unfished levels and a fishing mortality below natural mortality). Landings data indicate a clear shift from historically dominant large-bodied species to smaller taxa, reflecting target species depletions and regulatory changes. Despite life history parameters uncertainty, results were robust across alternative length-based approaches and consistently indicated widespread stock depletion. These findings highlight an urgent need for stronger management, including effective size limits, the protection of spawning aggregations, and retention of the export ban. Lifting the ban would likely increase fishing pressure and further accelerate declines of Palau’s already depleted reef fish populations.

Life-history characteristics of reef ocean perch (Helicolenus percoides) from south-east Australia - Nicholas J. Shelverton; Alyssa Marshell; Peter G. Coulson (Regional Studies in Marine Science, 2026)

Acoustic telemetry reveals spawning aggregation dynamics and management implications for longnose emperor (Lethrinus olivaceus) in Palau - Christina Muller Karanassos; Natalie S. Arnoldi; Louw Claassens; McQuinnley Mesengei; Alyssa Marshell; Nils C. Krueck; Barrett Wolfe (Fisheries Research, 2026)

Prevelance of the parasitic copepod Acanthochondria diastema Kabata, 1965 in wild populations of the southern sand flathead, Platycephalus bassensis - Peter G. Coulson; Jawahar G. Patil; Adam Davey; Alyssa Marshell (Estuarine, Coastal and Shelf Science, 2026)

Quantifying distinctions in the otolith shape of morphologically similar Sub-Antarctic grenadier species (Macrourus) to assess fishery observer identifications. - William A.J. Connor; Cara Masere; Peter G. Coulson; Alyssa Marshell (Fisheries Research, 2025)

Evaluating the effectiveness of artificial reefs in enhancing fisheries productivity and biodiversity in the Sea of Oman - Abdullah Al Kindi; Alyssa Marshell; Sachinandan Dutta (Estuarine, Coastal and Shelf Science, 2025)

Rapid diversification of grey mangroves ( Avicennia marina ) driven by geographic isolation and extreme environmental conditions in the Arabian Peninsula - Guillermo Friis; Edward G. Smith; Catherine E. Lovelock; Alejandra Ortega; Alyssa Marshell; Carlos M. Duarte; John A. Burt (Molecular Ecology, 2024)
Biological systems occurring in ecologically heterogeneous and spatially discontinuous habitats provide an ideal opportunity to investigate the relative roles of neutral and selective factors in driving lineage diversification. The grey mangroves ( Avicennia marina ) of Arabia occur at the northern edge of the species' range and are subject to variable, often extreme, environmental conditions, as well as historic large fluctuations in habitat availability and connectivity resulting from Quaternary glacial cycles. Here, we analyse fully sequenced genomes sampled from 19 locations across the Red Sea, the Arabian Sea and the Persian/Arabian Gulf (PAG) to reconstruct the evolutionary history of the species in the region and to identify adaptive mechanisms of lineage diversification. Population structure and phylogenetic analyses revealed marked genetic structure correlating with geographic distance and highly supported clades among and within the seas surrounding the Arabian Peninsula. Demographic modelling showed times of divergence consistent with recent periods of geographic isolation and low marine connectivity during glaciations, suggesting the presence of (cryptic) glacial refugia in the Red Sea and the PAG. Significant migration was detected within the Red Sea and the PAG, and across the Strait of Hormuz to the Arabian Sea, suggesting gene flow upon secondary contact among populations. Genetic‐environment association analyses revealed high levels of adaptive divergence and detected signs of multi‐loci local adaptation driven by temperature extremes and hypersalinity. These results support a process of rapid diversification resulting from the combined effects of historical factors and ecological selection and reveal mangrove peripheral environments as relevant drivers of lineage diversity.

Population genetic structure of a major reef-building coral species Acropora downingi in northeastern Arabian Peninsula - Felipe Torquato; Jessica Bouwmeester; Pedro Range; Alyssa Marshell; Mark A. Priest; John A. Burt; Peter R. Møller; Radhouan Ben-Hamadou (Coral Reefs, 2022)
Current seawater temperatures around the northeastern Arabian Peninsula resemble future global forecasts as temperatures > 35 °C are commonly observed in summer. To provide a more fundamental aim of understanding the structure of wild populations in extreme environmental conditions, we conducted a population genetic study of a widespread, regional endemic table coral species, Acropora downingi , across the northeastern Arabian Peninsula. A total of 63 samples were collected in the southern Arabian/Persian Gulf (Abu Dhabi and Qatar) and the Sea of Oman (northeastern Oman). Using RAD-seq techniques, we described the population structure of A. downingi across the study area. Pairwise G’st and distance-based analyses using neutral markers displayed two distinct genetic clusters: one represented by Arabian/Persian Gulf individuals, and the other by Sea of Oman individuals. Nevertheless, a model-based method applied to the genetic data suggested a panmictic population encompassing both seas. Hypotheses to explain the distinctiveness of phylogeographic subregions in the northeastern Arabian Peninsula rely on either (1) bottleneck events due to successive mass coral bleaching, (2) recent founder effect, (3) ecological speciation due to the large spatial gradients in physical conditions, or (4) the combination of seascape features, ocean circulation and larval traits. Neutral markers indicated a slightly structured population of A. downingi, which exclude the ecological speciation hypothesis . Future studies across a broader range of organisms are required to furnish evidence for existing hypotheses explaining a population structure observed in the study area. Though this is the most thermally tolerant acroporid species worldwide, A. downingi corals in the Arabian/Persian Gulf have undergone major mortality events over the past three decades. Therefore, the present genetic study has important implications for understanding patterns and processes of differentiation in this group, whose populations may be pushed to extinction as the Arabian/Persian Gulf warms.

Refuge-dependent herbivory controls a key macroalga on coral reefs - Laura D. Puk; Alyssa Marshell; John Dwyer; Nicolas R. Evensen; Peter J. Mumby (Coral Reefs, 2020)

Microherbivores are significant grazers on Palau’s forereefs - Noam T. Altman-Kurosaki; Mark A. Priest; Yimnang Golbuu; Peter J. Mumby; Alyssa Marshell (Marine Biology, 2018)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Interactions among chronic and acute impacts on coral recruits: the importance of size‐escape thresholds - Christopher Doropoulos; Selina Ward; Alyssa Marshell; Guillermo Diaz-Pulido; Peter J. Mumby (Ecology, 2012)
Newly settled recruits typically suffer high mortality from disturbances, but rapid growth reduces their mortality once size‐escape thresholds are attained. Ocean acidification (OA) reduces the growth of recruiting benthic invertebrates, yet no direct effects on survivorship have been demonstrated. We tested whether the reduced growth of coral recruits caused by OA would increase their mortality by prolonging their vulnerability to an acute disturbance: fish herbivory on surrounding algal turf. After two months' growth in ambient or elevated CO 2 levels, the linear extension and calcification of coral ( Acropora millepora ) recruits decreased as CO 2 partial pressure ( p CO 2 ) increased. When recruits were subjected to incidental fish grazing, their mortality was inversely size dependent. However, we also found an additive effect of p CO 2 such that recruit mortality was higher under elevated p CO 2 irrespective of size. Compared to ambient conditions, coral recruits needed to double their size at the highest p CO 2 to escape incidental grazing mortality. This general trend was observed with three groups of predators (blenny, surgeonfish, and parrotfish), although the magnitude of the fish treatment varied among species. Our study demonstrates the importance of size‐escape thresholds in early recruit survival and how OA can shift these thresholds, potentially intensifying population bottlenecks in benthic invertebrate recruitment.